PREDATION OF Boophilus microplus (CANESTRINI, 1887) (ACARI: IXODIDAE) TICK ENGORGED FEMALE BY THE ANT Pachycondyla striata (SMITH, 1858) (HYMENOPTERA: FORMICIDAE) IN PASTURES (Bioscience Journal, 2006)
Faced with difficulties in the chemical control of Boophilus microplus, this work intended to observe the principal predator of engorged females in pastures of the grass Brachiaria decumbens, at Juiz de Fora, MG, Brazil. A total of 300 engorged female were used, between six experimental repetitions during the winter of 1998 and the summer of 1998/1999. Such tick samples were released into the pastures every two weeks, being placed in clumps of B. decumbens and observed at intervals of two hours throughout the daytime. The ant Pachycondyla striata was confirmed as an important predator of the tick that fed on the engorged females in situ or taken to its colony. Predation was greater during the summer (50,5% of ticks released) than the winter (33,3%). It was concluded that this ant should be investigated further for possible future employment in the biological control of B. microplus in Brazil. UNITERMS: Tick, Boophilus microplus, Pachycondyla striata, Predation.